The Importance of Cultural Monuments in Greece: How the Cultural Management Is A Definitive Factor for The Sustainable Development in Region of Epirus? (Journal of Advanced Research in Social Sciences, 2019)
This paper is focused on the anthropology of space, in architectural and cultural monuments of the mountainous village of Konitsa. Epirus is region that presents a harmonious collaboration between nature and people. The purpose of the anthropological research approach was focused on the way in which the dynamics of cultural heritage are perceived by local residents.The main research question concerns the perceptions of the social actors of the village of Konitsa regarding the cultural monuments in the region. The methodology of fieldwork had as a key tool the use of interviews, charts, discussions with the locals, walks, tours and visits as well as observation of locations, people and monuments.The inhabitants currently living in the wider area of Konitsa, are directly related to the tangible reality of history, folklore and tradition of monuments, something that can be easily detected through a wide range of aspects of the region’s ‘’social life’’ (Appadurai & Kopytoff, 1986). Although the cultural and traditional heritage refer to the past, they have a significant impact on the present era and they also have the ability to determine the future. (Bulter & Rowlahds, 2012).The cultural management is an advantage of Konitsa and the cooperation with the social associations, for example agriculture partnerships, can reduce the unemployment as well as the immigration and help in the economic development. This research paper is based on the fieldwork and theoretical lessons in the Summer School Konitsa 2016 of Border Crossing Network.